Несимметричные приближения в пространстве Lp(t) - Литвин, Е.Г.; Поляков, О.В. (Український математичний журнал, 1999)
Введено поняття про (α,β)-норму у просторі Lp(t) функцій x(t), для яких ∫|x(t)|p(t)<∞
де p(t) — додатна вимірна функція. Встановлено критерій елемента найкращого (α,β)-наближення у просторі Lp(t). Отримано нерівності типу співвідношень двоїстості. We introduce the notion of (α,β)-norm in the space Lp(t) of functions x(t) for which ∫|x(t)|p(t)<∞ where p(t) is a positive measurable function. We establish a criterion for the element of the best (α,β)-approximation in the space Lp(t). We obtain inequalities of the type of duality relations.